Transformasi Peran Guru Sebagai Fasilitator Hubungan Sekolah dengan Masyarakat di Era Disrupsi - Abdi, Abdi Cahya Subekti; Rizal, Zacky Al-Ghofir El-Muhtadi; Khasanah, Nur (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
The era of disruption, marked by digital advancement, the Merdeka Belajar (Freedom to Learn) policy, and post-pandemic social changes, has transformed the teacher’s role from a mere transmitter of knowledge into a facilitator of relationships between schools and communities. This study employs a library research method to analyze the dynamics, driving factors, and implications of this transformation from the perspective of contemporary sociology of education. The findings reveal that teachers’ roles are increasingly oriented toward collaboration, participation, and cross-stakeholder partnerships, driven by technological innovation, social demands, and educational policies emphasizing autonomy and collective cooperation. Despite challenges such as increased workload, digital inequality, and ethical boundaries in online interactions, teachers act as agents of change who reconstruct educational social relations in more inclusive and participatory ways. This transformation underscores that teachers are not only adaptive to disruption but also serve as key drivers of education grounded in humanity, collaboration, and community values.